Microscopic approach for the n-d effective interaction - Tomio, Lauro [UNESP]; Frederico, T.; Delfino, A. (American Physical Society (APS), 1990)
A three-boson model is applied to the nucleon-deuteron (n-d) system to construct an effective energy-dependent two-body potential in configuration space. The three-nucleon observables at low energy are well reproduced with just one free parameter (related with the range of the nucleon-nucleon interaction). We show that the present results give support to a previous phenomenological n-d potential. © 1990 The American Physical Society.